SOCIAL CLASS INEQUALITY DEPICTED IN CHILDREN PICTURE BOOK THE RICH MAN AND THE MONKEY BY IDRIES SHAH: GENETIC STRUCTURALISM LUCIEN GOLDMANN’S PERSPECTIVE - Deviana Gita Tsaniah; Resneri Daulay (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2025)
This study uses genetic structuralism Lucien Goldmann's theory as a sociological framework. It aims to understand how class inequality is symbolically depicted through the characters' behavior and how shifting material conditions affect ideological transformation. Using a qualitative research design, this study conducted a careful textual analysis of the narrative, identifying ideological contradictions through a class-based worldview.This results show that the rich man and the monkey serve as symbolic representations of the oppressed class and the elite class, respectively. The monkey's initial plea highlights the structural exclusion of the lower class, while the rich man's moral crisis reflects contradictions in bourgeois consciousness. However, upon receiving the rich man's wealth, the monkey quickly adopts the attitudes and behaviors of the former elite, showing that material change alone does not guarantee ideological progress. The narrative reveals a cyclical pattern in which oppression is reproduced under new identities, confirming that without a transformation in collective consciousness, instead of erasing inequality, class mobility entrenches the existing hierarchical system. This study concludes that The Rich Man and The Monkey is more than a moral tale; it is a critical reflection on the persistence of class ideology